2017
DOI: 10.1177/0146167217744194
|View full text |Cite
|
Sign up to set email alerts
|

Facial First Impressions Across Culture: Data-Driven Modeling of Chinese and British Perceivers’ Unconstrained Facial Impressions

Abstract: People form first impressions from facial appearance rapidly, and these impressions can have considerable social and economic consequences. Three dimensions can explain Western perceivers' impressions of Caucasian faces: approachability, youthful-attractiveness, and dominance. Impressions along these dimensions are theorized to be based on adaptive cues to threat detection or sexual selection, making it likely that they are universal. We tested whether the same dimensions of facial impressions emerge across cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
179
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(213 citation statements)
references
References 61 publications
27
179
1
Order By: Relevance
“…Although we noted that some other studies have also found three dimensions underlying impressions of faces (Olivola, Eubanks, et al, 2014;Sutherland, Liu, et al, 2017;Wolffhechel et al, 2014), major models of facial first impressions are often couched in terms of two underlying dimensions Walker & Vetter, 2009), as is a leading model of intergroup perception (Fiske et al, 2007). This finding was by no means inevitable.…”
Section: Wider Implicationsmentioning
confidence: 68%
“…Although we noted that some other studies have also found three dimensions underlying impressions of faces (Olivola, Eubanks, et al, 2014;Sutherland, Liu, et al, 2017;Wolffhechel et al, 2014), major models of facial first impressions are often couched in terms of two underlying dimensions Walker & Vetter, 2009), as is a leading model of intergroup perception (Fiske et al, 2007). This finding was by no means inevitable.…”
Section: Wider Implicationsmentioning
confidence: 68%
“…It also agrees with the pattern found across culture: For example, Sutherland et al . () found similar impression dimensions for British and Chinese groups, but with the least cross‐cultural agreement on competence. Moreover, Sutherland, Oldmeadow, et al .…”
Section: Discussionmentioning
confidence: 90%
“…First, Zebrowitz, Franklin, Hillman, and Boc () have measured the degree to which individual observers agree with members of the same or different social groups, for example, finding that older and younger people do agree in their impressions of faces across age. Second, studies modelling group‐based impressions also usually cross‐validate these impression dimensions by constructing computer‐generated (Oosterhof & Todorov, ; Walker & Vetter, ) or morphed (Sutherland et al ., , ) faces directly from the models and then ascertaining that these faces are perceived as expected by new sets of observers. Third, the fact that facial impressions predict important social consequences in the real world is also suggestive that impressions must be consensual, at least to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…A second dimension is thought to reflect a target's ability to enact those intentions. Traits such as dominant, competent, or physically strong load on this dimension (Fiske, Cuddy, Glick, & Xu, ; Leary, ; Leyens et al, ; Oosterhof & Todorov, ; Sutherland et al, ; Todorov & Engell, ). Recent research including older targets among those being rated yielded a third dimension of “youthful/attractive” (Sutherland et al, ).…”
Section: Target Contributions To Impressionsmentioning
confidence: 99%
“…Three dimensions emerged when British perceivers evaluated British faces but only two when evaluating Chinese faces. Three dimensions emerged when Chinese perceivers evaluated British faces, versus four when evaluating Chinese targets (Sutherland et al, ).…”
Section: Moving Forwardmentioning
confidence: 99%